Association of Intracranial Hypertension With Calvarial and Skull Base Thinning. Issue 6 (July 2019) - Rabbani, Cyrus C.; Patel, Janaki M.; Nag, Amit; Schueth, Elizabeth; Saltagi, Mohamad Z.; Kao, Richard; Nelson, Rick F.
Abstract : Objective: Determine if patients with increased opening pressure (OP) on lumbar puncture (LP) have thinner calvaria and skull bases. Study Design: Retrospective cohort study. Setting: Tertiary referral center. Patients: Patients (≥18 yr of age) who had a recorded OP on LP and high-resolution computed tomography imaging of the head. Patient age, sex, body mass index were calculated. Intracranial hypertension (IH) was defined with an OP≥25 cm-H2 O and low intracranial pressure with an OP<15 cm-H2 O. Intervention: Measurement of calvarial, zygoma, and skull base thickness when blinded to OP with three-dimensional slicer and radiologic calipers. Main Outcome Measures: Association of calvarial, skull base, and zygoma thickness with OP and age. Results: Fifty-eight patients were included with a mean (SD) age of 53.1 (16.2) years and average (SD) body mass index of 30.1 (9.1) kg/m 2 . Patients with IH had thinner mean (SD) calvaria (3.01 [0.81] versus 2.70 [0.58] mm; p = 0.036) and skull bases (5.17 [1.22] versus 4.60 [1.42] mm; p = 0.043) when compared with patients without IH. The mean (SD) extracranial zygoma thickness was similar between the two groups (5.09 [0.76] versus 5.00 [0.73] mm; p = 0.56). General linear model regression demonstrated advancing age was associated with increasing calvarial thickness in patients without IH and calvarial thinning in patients with IH ( p = 0.038). Conclusion: IH is independently associated with intracranial bone (calvaria and skull base) thinning and not extracranial (zygoma) thinning. Skull thinning occurs with IH and advancing age. These findings support a possible role of increased ICP in the pathophysiologic development of spontaneous cerebrospinal fluid leaks.